2014
DOI: 10.1167/iovs.13-11740
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid Uptake, Processing, and Secretion in Human iPS-RPE Support the Visual Cycle

Abstract: iPS-RPE develops classic RPE characteristics and maintains expression of visual cycle proteins. The results of this study confirm that iPS-RPE possesses the machinery to process retinoids for support of visual pigment regeneration. Inhibition of all-trans retinyl ester accumulation by NEM confirms LRAT is active in iPS-RPE. Finally, the detection of 11-cis retinaldehyde in the culture medium demonstrates the cells' ability to process retinoids through the visual cycle. This study demonstrates expression of key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…iPS-RPE was derived as previously described. 11,12 Briefly, human iPS cells (IMR-90-1;WiCell Research Institute, Madison, WI, USA) were cultured iovs.arvojournals.org j ISSN: 1552-5783 on Matrigel-coated (BD Biosciences, San Jose, CA, USA) in sixwell plates and maintained in mTeSR1 medium (Stem Cell Technologies, Vancouver, BC, Canada). To initiate differentiation, The mTeSR1 medium was replaced with differentiation medium consisting of 10% knockout serum replacement (Life Technologies), 0.1 mM b-mercaptoethanol, 0.1 mM nonessential amino acids, 2 mM glutamine, and 10 lg/mL gentamicin in DMEM-F12 medium.…”
Section: Methods Cell Culture and Differentiation Of Ips Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…iPS-RPE was derived as previously described. 11,12 Briefly, human iPS cells (IMR-90-1;WiCell Research Institute, Madison, WI, USA) were cultured iovs.arvojournals.org j ISSN: 1552-5783 on Matrigel-coated (BD Biosciences, San Jose, CA, USA) in sixwell plates and maintained in mTeSR1 medium (Stem Cell Technologies, Vancouver, BC, Canada). To initiate differentiation, The mTeSR1 medium was replaced with differentiation medium consisting of 10% knockout serum replacement (Life Technologies), 0.1 mM b-mercaptoethanol, 0.1 mM nonessential amino acids, 2 mM glutamine, and 10 lg/mL gentamicin in DMEM-F12 medium.…”
Section: Methods Cell Culture and Differentiation Of Ips Cellsmentioning
confidence: 99%
“…[8][9][10] RPE derived from induced pluripotent stem cells (iPS-RPE) displays the phenotype and functions of in vivo RPE and provides a physiologically relevant cell type with which to study wound healing. 11,12 iPS-RPE was used to conduct in vitro wound healing assays. Expression and localization of b-catenin, e-cadherin, n-cadherin, and S100A4 were examined to confirm onset of EMT.…”
mentioning
confidence: 99%
“…Other Approaches: Stem cell therapy is being tested for the treatment of blinding disorders. Muniz et al utilized human pluripotent stem cells in-vitro and derived functional RPE capable of all-trans retinol uptake from the conditioned culture medium, processing it into 11-cis retinal for secretion (5). This study provided the proof of principle of using pluripotent skin cells (iPS) from a patient to generate iPS-RPE for intraocular or retinal injection.…”
Section: Strategies To Advance the Cure Of Blinding Afflictionsmentioning
confidence: 99%
“…47,48 In vitro assays have been developed to verify visual cycle function in iPSC-derived RPE cultures. While many research groups have efficiently developed iPSC-RPE cells, only a limited number have demonstrated the production of retinoids in these cultures.…”
Section: Retinoid Processing In Induced Pluripotent Stem Cell-derivedmentioning
confidence: 99%